Development of a one-step multiplex (RT)-PCR for simultaneous detection of virus-induced respiratory disease complex in dogs in Vietnam: https://doi.org/10.12982/VIS.2024.053 - Dao Huyen Tran,; Nguyen Tran Phuoc Chien,; Nguyen Thi Lan Anh,; Pham Cong Uan,; To My Quyen,; Nguyen Pham Nha Quan,; Chau Thi Huyen Trang,; Lam Thanh Nguyen, (Veterinary Integrative Sciences, 2024)
Canine infectious respiratory disease (CIRD) viruses, particularly canine distemper virus (CDV), canine adenovirus type 2 (CAV-2), and canine parainfluenza virus (CPIV), are the primary agents responsible for respiratory diseases in dogs. A dog can be infected with a single or multiple viruses with similar clinical signs. Although CIRD is globally prevalent in dogs, investigation into the causative viruses in Vietnam remains limited. This study aims to identify the presence of CIRD virus(es) in dogs via molecular detection. Three primer sets were newly designed and applied into (RT)-PCR reaction to detect viral genes of CDV, CAV-2, and CPIV in a commercial vaccine (Vanguard® Plus 5/L, Zoetis, USA). Both simplex and multiplex (RT)-PCR reactions using the three primer sets could detect the presence of CAV-2, CDV, and CPIV in the vaccine sample. Subsequently, the applicability of the one-step multiplex (RT)-PCR was demonstrated to test for 27 clinical nasal swab samples collected from dogs suspected of having CIRD. The results showed that our (RT)-PCR could detect CIRD virus(es) in all tested clinical samples. PCR amplicons for each representative CAV-2, CDV, and CPIV were selected for sequencing and showed high genetic similarity to respective field viruses. In conclusion, this study successfully developed a one-step multiplex (RT)-PCR reaction to detect and differentiate causative viruses of CIRD in dogs.